Analysis of students’ scientific argumentation using the SOLO taxonomy on hydrocarbon material through a socio-scientific issues (SSI) approach - Tritiyatma Hadinugrahaningsih; Yuli Rahmawati; Rika Siti Syaadah; Adam Julio Waskito; Fatikhah Widya Rahmadani; Dzakiyyah Alfina Hanum; Devita Marlina Vanessa (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2026)
This study aims to identify the argumentation profiles of students on the topic of carbon compounds using a socio-scientific issues (SSI) approach. The research was conducted at one of public senior high schools in Tangerang involving 32 twelfth-grade students. A mixed methods were employed. The research instruments included observation sheets, reflective journals, argumentation tests, student worksheets, and interviews. The results indicate that chemistry learning on carbon compounds through the socio-scientific issues (SSI) approach created a more engaging learning environment, as the discussions and problem topics were closely related to everyday life. The students’ argumentation profiles generally demonstrated multi-structural abilities in the components of evidence and reasoning, with respective percentages of 81% and 50%. Meanwhile, the components of rebuttal and claim were still at pre-structural and unistructural levels, with a unistructural percentage of 50% and 72%, respectively. These findings suggest that although the Socio-scientific Issues (SSI) approach has been effective in developing students' abilities to provide evidence and reasoning, their skills in constructing strong claims and presenting appropriate rebuttals still require further improvement.